Transport of Young Veal Calves: Effects of Pre-transport Diet, Transport Duration and Type of Vehicle on Health, Behavior, Use of Medicines, and Slaughter Characteristics - Marcato, Francesca; van den Brand, Henry; Kemp, Bas; Engel, Bas; Wolthuis-Fillerup, Maaike; van Reenen, Kees (Frontiers in Veterinary Science, 2020)
The aim of this study was to investigate effects of different early life transport-related factors on health, behavior, use of medicines and slaughter characteristics of veal calves. An experiment was conducted with a 2 × 2 × 2 factorial arrangement with 3 factors: 1) provision of rearing milk or electrolytes before transport, 2) transport duration (6 or 18 h), and 3) type of vehicle (open truck or conditioned truck). The study included male Holstein-Friesian and cross-bred calves (N = 368; 18 ± 4 days; 45.3 ± 3.3 kg). Data on health status of calves were collected at the collection center and at the veal farm until week 27 post-transport. Behavior of calves was recorded during transport and at the veal farm until week 13 post-transport. Use of herd and individual medical treatments was recorded at the veal farm. The prevalence of loose or liquid manure at the veal farm from day 1 until week 3 post-transport was lower in electrolyte-fed calves transported in the conditioned truck compared to electrolytes-fed calves transported in the open truck or milk-fed calves transported in both the conditioned and open truck (Δ = 11% on average; P = 0.02). In comparison with the open truck, calves transported in the conditioned truck had lower prevalence of navel inflammation in the first three weeks post-transport (Δ = 3 %; P = 0.05). More milk-fed calves received individual antibiotic treatments compared to electrolyte-fed calves at the veal farm (P = 0.05). In conclusion, the transport-related factors examined in the present study affected health and behavior of calves in the short-term, but there was no evidence for long-term effects. It remains unknown why no long-term effects were found in this study. Perhaps this absence of transport-related effects was due to multiple use of medical treatments in the first weeks at the veal farm. Alternatively, it might be that the collective effects of the transition from the dairy farm to the veal farm, and of the husbandry conditions during the subsequent rearing period, on the adaptive capacity of calves were so large that effects of individual transport-related factors were overruled.